(untitled) (Journal of Scientific Research, 2018)
Thin layer chromatography (TLC), a tool for defining identity, purity, and quantitation of a compound, has also been proved useful for monitoring the progress of a chemical reaction. However, the technique is yet to be exploited for investigating the kinetics of a reaction systematically. In this work, we used TLC for measuring the time for consumption of a reactant in Michael addition reaction of acetylacetone with 2-cyclohexene-1-one. Average rate of the model reaction was determined using a definite initial concentration of acetylacetone for a series of catalyst systems like NaOH, 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), DBU based protic ionic liquids (PILs) 1,8-diazabicyclo[5.4.0]undec-7-ene-8-ium hydroxide ([HDBU]OH) and 1,8-diazabicyclo[5.4.0]undec-7-ene-8-ium acetate ([HDBU]CH3COO), a DBU based aprotic ionic liquid (AIL), 8-hexyl-1,8-diazabicyclo [5.4.0]undec-7-ene-8-ium hydroxide ([C6DBU]OH), and binary systems of the ionic liquids with molecular solvents, such as, water, DBU, and acetic acid. The kinetic data on the performance of the chosen catalysts were interpreted on the basis of the established mechanism of the reaction. Finally, the prospect of the method based on TLC as a suitable technique for kinetic study of chemical reactions has been discussed.